Rule Of Law Mahkamah Syariah Aceh - Seri Mughni Sulubara; Murthada Murthada (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
Rule of law is a circus that aims to enforce the law in accordance with existing laws and regulations. The function of the Rule of Law is essentially a formal guarantee of a